Analisis Pengaruh Kepuasan Pelanggan Terhadap Pelayanan Jasa Penyeberangan PT. ASDP Indonesia Ferry (Persero) Cabang Bakauheni. - Suwandi SUWANDI (SOSIALITA, 2010)
PT. ASDP Indonesia Ferry (Company Limited) as one of trusted sea transportation service providers of the society is asked to repair and improve the customer’s safety and comfort. The problem gap between service which is got by customer and the quality of service which is given must be repaired in order to make the customer get the best service. The success of giving the qualified public service is not only on the success of providing product and service, but also on problem which is more fundamental that is how to satisfy society as the customer. Customer must be satisfied indeed; otherwise they will leave the company and cause decreasing of profit even lost. The problem in this research is whether there is relationship between customer satisfaction toward PT. ASDP Indonesia Ferry (Company Limited) transportation service at Branch of Bakauheni, the objective of this research is to know whether there is relationship customer satisfaction with PT. ASDP Indonesia Ferry (Company Limited) transportation service at Branch of Bakauheni and to know how much customer satisfaction influences the service provided by PT. ASDP Indonesia Ferry (Company Limited) at branch of Bakauheni. Qualitative analysis is toward every indicator, the result is got from all customer satisfaction level indicators which are on dissatisfaction category, also for all transportation service scoring indicators which is on bad category. The conclusion of this research is there is positive relationship which is insignificant between transportation customer satisfaction with transportation service which is shown by correlation coefficient, 0.1456, that is why the relationship includes very low category. It is between 0.00 – 0.199, and contribution (influence) of customer satisfaction (X) toward transportation service (Y) = KP = (0.1456)2 x 100% = 2.12 %, means transportation service is determined by customer satisfaction, 2.12%. the implication which must be paid attention and done by company to improve customer number is PT. ASDP Indonesia Ferry (Company Limited) at Branch of Bakauheni should understand customer need of good service. Moreover, company must repair the customer service also the facility which is on port and ferry, since customer is very important factor in a company, also improve the quality of transportation service, and the leader of PT. ASDP Indonesia Ferry (Company Limited) at Branch of Bakauheni needs to listen to his employee in process of taking the policy, in order to make policy which is able to be implemented and get support from his own employee.